A camera based method for assessing surf amenity of submerged nearshore structures in a wave basin by quantifying wave breaking - Michael E. Thompson; Alex Atkinson; Evan Watterson; Nick Naderi; Heiko Loehr; Tom E. Baldock (Ocean Engineering, 2023)

The Ancient Tree Inventory: a summary of the results of a 15 year citizen science project recording ancient, veteran and notable trees across the UK - Victoria Nolan; Tom Reader; Francis Gilbert; Nick Atkinson (Biodiversity and Conservation, 2020)
Ancient, veteran and notable trees are ecologically important keystone organisms and have tangible connections to folklore, history and sociocultural practices. Although found worldwide, few countries have such a rich history of recording and treasuring these trees as the UK, with its extensive Royal and aristocratic land ownership, unique land management methods and long-standing interest in natural history and species record collecting. As a result, the UK has collated an extensive database of ancient, veteran and notable trees called the Ancient Tree Inventory (ATI). The ATI is the result of a successful, long-term citizen science recording project and is the most comprehensive database of ancient and other noteworthy trees to date. We present here the first review of the ATI in its entirety since its initiation in 2004, including summaries of the UK ancient, veteran and notable tree distributions, the status and condition of the trees, and key information about the recording process and maintenance of the database. Statistical analysis of components of the dataset, comprising 169,967 tree records, suggest there are significant differences in the threats, size, form and location of different types of trees, especially in relation to taxonomic identity and tree age. Our goal is to highlight the value of the ATI in the UK, to encourage the development of similar ancient tree recording projects in other countries, and to emphasise the importance to conservation of continued efforts to maintain and expand databases of this kind.

Eradicating multiple invasive species on inhabited islands: the next big step in island restoration? - Alistair S. Glen; Rachel Atkinson; Karl J. Campbell; Erin Hagen; Nick D. Holmes; Bradford S. Keitt; John P. Parkes; Alan Saunders; John Sawyer; Hernán Torres (Biological Invasions, 2013)